Frontiers of Materials Science - Gu, Binglin; SpringerLink (Online service) (Beijing : Higher Education Press : Imprint: Higher Education Press, co-published with Springer.)
Frontiers of Materials Science is a peer-reviewed international journal that publishes high quality reviews/mini-reviews, full-length research papers, and short Communications recording the latest pioneering studies on all aspects of materials science. It aims at providing a forum to promote communication and exchange between scientists in the worldwide materials science community. The subjects are seen from international and interdisciplinary perspectives covering areas including (but not limited to): Biomaterials including biomimetics and biomineralization Nano materials Polymers and composites New metallic materials Advanced ceramics Materials modeling and computation Frontier materials synthesis and characterization Novel methods for materials manufacturing Materials performance Materials applications in energy, information and biotechnology.
Keywords: Materials science; Materials Science, general